Effect‐modifying role of education and crystalized intelligence on the association of amyloid pathology and cognitive function: Neuropsychiatry and behavioral neurology/presymptomatic disease/prodromal disease/prodromal states. (7th December 2020) - Udeh‐Momoh, Chinedu T.; Zheng, Bang; Price, Geraint J.; Watermeyer, Tam J.; de Jager, Celeste A.; Robb, Catherine; Giannakopoulou, Parthenia; Su, Bowen; Saad, Ziad; Fogle, Michael; Ford, Jamie; Ritchie, Craig W.; et al.
Abstract: Background: Cognitive reserve factors reflecting innate (crystallized intelligence) and derived (educational attainment) cognitive capacity are shown to be associated with preservation of cognitive function and delayed decline. Yet little information is available on how these static measures of reserve themselves are associated with cerebral amyloid burden and influence its effect on neurocognitive performance. Methods: In the deeply‐phenotyped CHARIOT:PRO substudy, 501 cognitively healthy individuals aged 60‐85 years had available information on ApoE genotype (carrier vs non‐carrier), brain PET‐scan/CSF‐derived amyloid load (positive vs negative), education attainment, premorbid intelligence measured by the National Adult Reading Test (NART), and cognitive performance via the multi‐domain Repeatable Battery Assessment of Neuropsychological Status (RBANS) measured at two time‐points (average 3.5 months apart). Linear mixed models were used to independently examine the effect modifying role of education and intelligence as measures of cognitive reserve on the association of amyloid status and cognitive function. Results: There was an effect modification in the association of amyloid status and global cognition (total RBANS score) by both intelligence and Education in mutually adjusted models accounting for age, sex and ApoE. The effect modification was more pronounced for intelligence. RBANS total score was lower in participants who were amyloid positive (vs negative) among those with lower than median intelligence quotient (mean difference in RBANS Z‐score by amyloid status ‐0.2 (95% CI ‐0.35, ‐0.04)). The inverse association between amyloid positivity and global cognition disappeared among those with higher than median intelligence (mean difference in RBANS Z‐score by amyloid status 0.01 (95% CI ‐0.16, 0.18)), P‐value for interaction <0.001. Correspondingly, mean difference in RBANS Z‐score for amyloid positivity (vs negativity) was ‐0.18 (95% CI ‐0.36, 0.00) for participants with below median education, and ‐0.07 (95% CI ‐0.24, 0.09) for participants with above median education attainment, P‐value for interaction 0.19. Further adjustment for body mass index, smoking, physical activity, systolic blood pressure and diabetes did not have a remarkable effect on the findings. Conclusions: Our results support the hypothesis that although education and intelligence are both associated with higher cognitive reserve, crystalized intelligence provides more resilience against the neurodegenerative effect of amyloid pathology on global cognition.